Direct seeded rice cultivation method: a new technology for climate change and food security - Marasini, S; Joshi, TN; Amgain, LP (Journal of Agriculture and Environment, 2018)
Rice (Oryza sativa) is the major food crop in terms of production and economy and grown in all ecological regions of Nepal. Rice is cultivated traditionally through transplanting of 20-25 days old seedling in the country. Due to unavailability of suitable technology for rice cultivation, there is a huge yield gap in rice production of Nepal. Country has made target of self-sufficiency in rice production by 2020 AD. This target can be achieved through adoption of Direct seeded rice cultivation technology of rice cultivation which also helps to adapt in the climate change scenario of Nepal. Due to issues of water scarcity and expensive labour, direct seeded rice cultivation technology is adopting worldwide. Direct seeded rice is a resource conservation technology and reduces water and labor use by 50%. Productivity of DSR is 5-10% more than the yield of transplanted rice. It offers a very exhilarating opportunity to improve water and environmental sustainability. Methane gas emissions is lower in DSR than with conventionally tilled transplanted puddle rice. It involves sowing pre-germinated seeds into a puddled soil surface (wet seeding), standing water (water seeding) or dry seeding into a prepared seedbed (dry seeding). Precise water management, particularly during crop emergence phase (first 7-15 days after sowing), is crucial in direct seeded rice. Furthermore, weed infestation is the major problem, which can cause large yield losses in direct seeded rice. Weed management in DSR can be done through chemical, hand weeding or stale seed bed method.